PENGEMBANGAN APLIKASI KAMUS INDONESIA JAWA MENGGUNAKAN ALGORITMA SEQUENTIAL SEARCH BERBASIS WEB - Galang Rangga Bintang Baruna; Alfannisa Annurrullah Fajrin (LPPM Universitas Putera Batam, 2025)
This study aims to create an Indonesian-Javanese dictionary web based application using the Sequential Search algorithm. The application is designed to help younger generations understand the Javanese language, including its hierarchical speech levels (unggah-ungguh), which are becoming less commonly used, particularly in multicultural cities like Batam. The Sequential Search algorithm is implemented to simplify word searches sequentially. The application is developed using PHP, the Laravel framework, and PostgreSQL database, covering 1,500 basic vocabularies. The interface is designed to be simple, allowing users to perform two-way translations between Indonesian and Javanese quickly. Testing results show that the application can provide accurate translations and offer suggestions for words not found. With these features, the application is expected to serve as an efficient Javanese language learning tool while preserving Javanese cultural values among younger generations. Keywords:Indonesian-Javanese Dictionary, Sequential Search, Web Application, Language Learning, Cultural Preservation, Javanese Speech Levels, PHP, Laravel, PostgreSQL.